Sistem Bagi Hasil Terhadap Pengelolaan Badan Usaha Milik Desa (Studi pada BUMDesa Karang Anyar Langsa Aceh) - Tarlis, Andi; Agustina, Zera (EKOBIMA, 2024)
Indonesia is a country whose territory is divided into provincial areas. Provincial areas are further divided into Regency and City areas. Each Province, Regency, and City area has a regional government regulated by Law. The study entitled Profit Sharing System for the Management of Village-Owned Enterprises Study on BUMDesa Karang Anyar Langsa Aceh). The objectives of the study are: 1) to determine the effectiveness of the management of Village-Owned Enterprises in Karang Anyar Village, Aceh Province. 2) to determine the profit sharing system for the management of Village-Owned Enterprises in Karang Anyar Village, Aceh Province. The results of the study are 1) in its implementation, the management of Karang Anyar Village-Owned Enterprises has been running well, such as in Planning, namely the management of Village-Owned Enterprises has planned all Village-Owned Enterprise programs carefully, in organizing all managers of Village-Owned Enterprises have carried out the duties of each of their responsibilities well, in its implementation, Village-Owned Enterprises have been effective in running Village-Owned Enterprise programs even though there are still some obstacles, and in the evaluation, 2) the presence of Village-Owned Enterprises in the Karang Anyar Village community has become a forum for the community's economy and is able to empower the community and reduce unemployment among the Karang Anyar community, especially in Langsa City, this is proven by the community being involved in making activities such as chips businesses, tempeh businesses and others.